New Year Greetings from Science Insights Education Frontiers - Zhou, Longjun (Science Insights Education Frontiers, 2024)
The year of of 2023 was supposed to be a year full of hopes and with the promise that everything would return to the right track. At the end of the year, however, we realized that the world was far away from the right track. Instead, it underwent a turbulent period, becoming more unstable, uncertain, and unpredictable: Geopolitical conflicts continued to escalate, and the humanitarian crises were deteriorating, with no signs of the Russian-Ukrainian war coming to an end or Palestinian-Israeli tension subsiding; The world economy was slowing down, facing the dual challenges of low growth and high inflation; Natural and climate change-induced disasters arose one after another, like the devastating earthquake in Turkey, once-in-a-century drought in the Amazon rainforest, and the raging floods in the Horn of Africa, to name a few.